Pengelolaan Manajemen Keuangan Guna Meningkatkan Sarana dan Prasarana yang Ada di SDN Tembok Dukuh 3 Surabaya - Shinta Salsabila (Universitas 45 Surabaya, 2023)
Management of financial management is an activity that plans, organizes, directs, and supervises all financial activities in an institution, by knowing how to manage finances properly, the income or expenditure of an agency will be easier to find out. The purpose of this research article is to find out an overview of improving facilities and infrastructure through managing financial management in Tembok Dukuh 3 Elementary School. The results of this study indicate that financial management in schools starting from designing plans to evaluating the use of school funds is quite good. The implication of this research is that school principals must monitor staff / employees more in order to prevent mistakes in bookkeeping.